Power electronics and motor drives - Wilamowski, Bogdan M.; Irwin, J. David, 1939- (CRC Press, 2011)
The Industrial Electronics Handbook, Second Edition combines traditional and newer, more specialized knowledge that will help industrial electronics engineers develop practical solutions for the design and implementation of high-power applications. Embracing the broad technological scope of the field, this collection explores fundamental areas, including analog and digital circuits, electronics, electromagnetic machines, signal processing, and industrial control and communications systems. It also facilitates the use of intelligent systems-such as neural networks, fuzzy sys.
Keywords: Power electronics.; Electric motors -- Power supply.; Electric power supplies to apparatus -- Design and construction.; elektronické knihy; electronic books